2020
DOI: 10.1037/dev0000885
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the Children’s Future Thinking Questionnaire: A reliable and valid measure of children’s future-oriented cognition.

Abstract: Future-oriented cognition (planning, prospective memory, episodic foresight, saving, and delay of gratification) involves a critical set of skills that children must develop for successful daily functioning. The current study developed the Children's Future Thinking Questionnaire (CFTQ), a parent-report on 3-to 7-year-olds' future-oriented cognition. The CFTQ showed high internal consistency and detected development of future-oriented cognition (Study 1; N = 145). Study 2 (N = 255) showed high internal consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 56 publications
(110 reference statements)
2
44
2
Order By: Relevance
“…Further, none of the behavioural measures (aside from one measure of episodic foresight) was significantly correlated with the parent questionnaire after age and general language ability were controlled for. Mazachowsky and Mahy (2020) further found that results from the questionnaire were correlated with age, suggesting, as previous studies had found, that performance on these types of tasks improve with age, thus finding further support for their questionnaire. Despite the lack of statistically significant findings regarding the correlations between the behavioural measures and the parent questionnaire, all of the correlations were in the direction the researchers expected, which was interpreted to mean that the findings provide evidence that the questionnaire is a valid measure of future-oriented thinking in children.…”
Section: Savingsupporting
confidence: 77%
See 4 more Smart Citations
“…Further, none of the behavioural measures (aside from one measure of episodic foresight) was significantly correlated with the parent questionnaire after age and general language ability were controlled for. Mazachowsky and Mahy (2020) further found that results from the questionnaire were correlated with age, suggesting, as previous studies had found, that performance on these types of tasks improve with age, thus finding further support for their questionnaire. Despite the lack of statistically significant findings regarding the correlations between the behavioural measures and the parent questionnaire, all of the correlations were in the direction the researchers expected, which was interpreted to mean that the findings provide evidence that the questionnaire is a valid measure of future-oriented thinking in children.…”
Section: Savingsupporting
confidence: 77%
“…To the best of my knowledge, there appears to be only two studies which measure both saving and PM among preschoolers (Chernyak et al, 2017;Mazachowsky & Mahy, 2020). Chernyak et al (2017) and Mazachowsky and Mahy (2020) do not report the relation between the saving and PM tasks, so no conclusions can be drawn about the relation between the two future-oriented skills. The study conducted by Mazachowsky and Mahy (2020) was described above.…”
Section: Saving and Pmmentioning
confidence: 98%
See 3 more Smart Citations